PENGEMBANGAN PLATFROM RUANG KERJA DIGITAL BAHASA ARAB DAN UMRAH DALAM MENINGKATKAN INOVASI BIMBINGAN HAJI DI EL HARAMAIN WISATA BANDUNG, JAWA BARAT - Rustiman, Uus; Helen, Afrida; Firmansyah, Eka Kurnia (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
The community service activity carried out is the development of an Arabic and Umrah digital workspace platform to increase innovation in Hajj guidance at El Haramain Wisata Bandung. The platform includes various key features such as Arabic learning modules, Umrah and Hajj guides, interactive maps, and discussion forums. Testing was conducted to ensure the functionality of the platform, which resulted in positive feedback from users. The training held ensures optimal use of the platform by congregants and mentors. This activity proves that digital technology can provide significant benefits in providing Hajj and Umrah guidance services, increasing information accessibility, structured information management, as well as time and cost efficiency